Sputum Smear Conversion During an Alternative Method for Providing "Directly Observed Therapy Short Course" In A Rural Setup Through Mobile Team - Lalit Singh; Anurag Agarwal; Anurag Srivastava (Medsci Publications, 2014)
Background: Tuberculosis is a disease as old as the history of mankind. Nothing substantial could be done by the National Tuberculosis Control Program, launched in our country about 6 decades back. According to a report in India, only 30% TB cases are diagnosed and of them only 35% take treatment for adequate duration. This study was conducted to know sputum conversion of supervised short course chemotherapy for pulmonary tuberculosis. Methods: The study was carried out on rural patients of Bareilly district. The patients were divided in two groups. Group A received drugs under supervision and Group B took conventional domiciliary treatment. In this study supervision was done by a 'designated' person who was usually parents, spouse, sibling or children and if no one was available or not found intelligent enough to do this job, a friend of patient living in the village was considered. Result: The sputum conversion was significantly faster in group A as compared to group B; but at 10th week the difference between the two groups became non-significant. The significance was further lost at 3 months, as 100% patients in both groups converted to negative and remained sputum negative at the end of 6 months. Conclusion: The sputum conversion was significantly faster in patient received anti-tuberculosis drugs under supervision as compared to patient who took conventional domiciliary treatment. The present study further supports the fact that DOTS with daily supervision is an effective treatment for tuberculosis.